Effects of the increase in CO2 and temperature on the carbon acquisition and assimilation mechanisms in polar macroalgae - Íñiguez Moreno, Concepción (UMA Editorial, 2016)
Ocean acidification and warming are affecting with special intensity polar regions. The coastal areas are dominated by dense macroalgal communities which represent a major trophic contribution to these systems and have a dominant role in carbon fluxes at regional scale. These macroalgae are expected to be directly affected by the increases in CO2 and temperature. The aim of this thesis is to characterise the physiological acclimation response of ecologically relevant polar seaweeds to an increase in temperature and CO2 to the levels expected by the end of this century. The species-specific differences in their acclimation mechanisms to increased CO2 and temperature will determine which species will benefit from the projected environmental scenario, and which others will be more negatively affected or not altered, enabling to identify winner and loser species as well as the degree of change expected in the community. For this purpose, different experiments using ecologically relevant Arctic and Antarctic macroalgae were done, consisting on the acclimation of thalli to an increase in CO2 and temperature. The results of this thesis have shown that the effects of elevated CO2 on the growth rate of polar macroalgae are species-specific, and that usually do not parallel the effects on photosynthesis. Instead, changes in growth rate were due to a reorganization of the energetic and carbon budget of the cell. Carbon fixation rates of all analysed Arctic species were not altered by increased CO2 levels, indicating that their photosynthesis must be C-saturated at current CO2 conditions. Moreover, all analysed red and brown seaweeds possess Rubiscos with a Kc for CO2 at 4°C of about 2-4 μM. Thus, their Rubiscos are saturated at 22 μM CO2, which is the concentration that corresponds to air-equilibrated seawater at 4°C. This significant increase in the affinity for CO2 at lower temperature observed in all analysed species suggest that polar seaweeds are more likely to possess C-saturated photosynthetic rates than temperate species at their usual environmental temperature, independently of their ability to use HCO3- for photosynthesis. The majority of the analysed polar seaweeds would need more than 1000 ppm CO2 to down-regulate their carbon concentrating mechanisms (CCMs), despite the observed high affinity for CO2 of their Rubiscos at low temperature. This highlights the importance of CCM operation in polar environments as part of a mechanism that ensures high photosynthetic rates in cold waters, of the same order of magnitude as those from temperate latitudes at their respective environmental temperature The results of this thesis provide novel and valuable data on the knowledge of cellular carbon fluxes, biochemical composition, physiology and photochemical performance, carbon acquisition and assimilation mechanisms and transcriptomic responses in polar seaweeds as they are affected by ocean acidification and warming. It includes a novel in-depth analysis of Rubisco kinetics that helps to understand the adaptation mechanisms to polar environments.
Keywords: Efecto invernadero - Aspectos ambientales - Tesis doctorales; Global change; Tesis doctoral; Seaweed; Temperature; Ocean acidification; Photosynthesis